DEVELOPMENT OF A WHATSAPP GATEWAY-BASED INFORMATION SYSTEM FOR MANAGING REQUESTS AND CUSTOMER SERVICES FOR REFILLED GALLON WATER ( CASE STUDY: BRYANRO) - Fauzan Respati Indira; Nardiono (STMIK Indonesia Banda Aceh, 2026)
Human trafficking is a form of crime that threatens human rights and negatively impacts social life (UNODC, 2024; IOM, 2023). Prevention efforts are not only carried out through law enforcement but also require the role of education in building legal awareness, humanitarian values, and the community's ability to recognize various forms of human trafficking (UNESCO, 2023; Kemendikbudristek, 2022). This study aims to analyze the role of education in preventing human trafficking in Indonesia and identify challenges in implementing prevention education in schools and communities. This study used a library research method with a qualitative descriptive approach. Data were obtained from laws and regulations, books, scientific articles, and other relevant documents. The results show that education plays a strategic role in improving legal literacy, shaping students' character, and instilling awareness of the dangers of human trafficking from an early age (Lickona, 1991; UNESCO, 2023). Integrating material on human rights, child protection, and the dangers of human trafficking into the learning process can increase students' awareness of various crime modes (UNICEF, 2023). However, the implementation of preventive education still faces various obstacles, such as limited teaching materials, a lack of educator competence, and minimal collaboration between educational institutions, the government, and the community (Kemendikbudristek, 2022). Therefore, curriculum strengthening, educator capacity building, and cross-sectoral collaboration are needed so that education can function optimally as a preventive strategy in preventing human trafficking in Indonesia.